The Role of Vitamin D Receptor Gene Polymorphisms in Colorectal Cancer Risk - Messaritakis, Ippokratis (Cancers (Basel), 2020)
Vitamin D deficiency has been associated with increased colorectal cancer (CRC) incidence risk and mortality. Vitamin D mediates its action through the binding of the vitamin D receptor (VDR), and polymorphisms of the VDR might explain these inverse associations. The aim of the study was the investigation of the relevance of rs731236; Thermus aquaticus I (TaqI), rs7975232; Acetobacter pasteurianus sub. pasteurianus I (ApaI), rs2228570; Flavobacterium okeanokoites I (FokI) and rs1544410, Bacillus stearothermophilus I (BsmI) polymorphisms of the VDR gene to colorectal carcinogenesis (CRC) and progression. Peripheral blood was obtained from 397 patients with early operable stage II/III (n = 202) and stage IV (n = 195) CRC. Moreover, samples from 100 healthy donors and 40 patients with adenomatous polyps were also included as control groups. Genotyping in the samples from patients and controls was performed using polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP). A significant association was revealed between all four polymorphisms and cancer. Individuals with homozygous mutant (tt, aa, ff or bb) genotypes were more susceptible to the disease (p < 0.001). All of the mutant genotypes detected were also significantly associated with stage IV (p < 0.001), leading to significantly decreased survival (p < 0.001). Moreover, all four polymorphisms were significantly associated with KRAS (Kirsten ras oncogene) mutations and Toll-like receptor (TLR2, TLR4 and TLR9) genetic variants. In multivariate analysis, tt, aa and ff genotypes emerged as independent factors associated with decreased overall survival (OS) (p = 0.001, p < 0.001 and p = 0.001, respectively). The detection of higher frequencies of the VDR polymorphisms in CRC patients highlights the role of these polymorphisms in cancer development and progression.